2013
DOI: 10.1155/2013/510298
|View full text |Cite
|
Sign up to set email alerts
|

The GenusSpilanthesEthnopharmacology, Phytochemistry, and Pharmacological Properties: A Review

Abstract: Spilanthes spp. are popular, over-the-counter remedies; they are sold over the internet under various names and are widely used in traditional medicine in various cultures. This review will summarize the important reports on the ethnopharmacology, botany, phytochemistry, and pharmacological properties as described in the literature from recent years (1920 to 2013). Spilanthes spp. are used for more than 60 types of disorders. They are reported to contain a number of biologically active phytochemicals, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 98 publications
(104 reference statements)
3
59
0
5
Order By: Relevance
“…Several phytochemicals, such as matrine, may provide a new therapeutic method for cancer treatment by inducing apoptosis [31][32][33][34]. In the present study, the apoptosis of WM130-treated HCC cells and the expression of apoptosis-related factors were examined.…”
Section: Discussionmentioning
confidence: 94%
“…Several phytochemicals, such as matrine, may provide a new therapeutic method for cancer treatment by inducing apoptosis [31][32][33][34]. In the present study, the apoptosis of WM130-treated HCC cells and the expression of apoptosis-related factors were examined.…”
Section: Discussionmentioning
confidence: 94%
“…Due to uncontrolled proliferation of cancer cells, one of the important properties of anticancer drugs is thought to be successful proliferation inhibition and apoptosis induction [17,18]. It is reported that promotion of apoptosis is partially responsible for cancer suppression caused by some dietary phytochemicals such as matrine, which provides a new therapeutic strategy for reducing the incidence of cancers [19,20,21,22]. However, several experimental studies showed that not all phytochemicals are good options to prevent the development of cancers because of underwhelming anticancer activities and toxicity problems.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in 2011, isolation of an isoprene derivative from methylanthranilate with antinociceptive properties (Radulović et al, 2011) coming from the essential oil from leaves of Choysia ternata (Rutaceae) was reported. Later, a QSAR study with different esters from anthranilate report as that isopropyl, methyl, and propyl N-methylantharanilates are more potent antinociceptive than morphine and are non-toxic (Pinheiro et al, 2014). The mechanism of action could be different to the one exhibited by alkamides of the spilanthol type, mechanism which seems to directly involve neurons (Bryant & Mezine, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Plants with these types of physiological effect are used in traditional medicine as analgesics or for toothache treatments. The most wellknown plants with these activities are species from the Piperaceae family (Parmar et al, 1997), genus Spilanthes (Asteraceae) (Paulraj et al, 2013), some species of Zanthoxylum (Rutaceae) (Caolo & Stermitz, 1979), and latex from several species of the Euphorbiaceae family (Szolcsanyi et al, 1990). Other bioactive compound is capsaicin from fruit of Capsicum (Solanaceae) (Sharma et al, 2013), but the sensation caused is more burning than analgesic.…”
Section: Introductionmentioning
confidence: 99%